The functional directions and features of the market of construction materials in the modern economy - Raihanova, G.A.; Gazizova, M.R.; Zharasbaeva, A.Zh. (BUKETOV BUSINESS REVIEW, 2017)
Products of the market of construction materials are considered in this article. Two of their groups are considered for the purpose of production of qualitative construction materials. Features of signs of classification of activities are presented at the market of construction materials. The features of formation of system of sales in the building materials market are analyzed. The formation of a range of building materials is a process of selection, differences, groups, and the creation of a range of construction materials in accordance with demand and in order to its satisfaction, which is part of the assortment policy. The main directions of the assortment policy of the enterprise are considered. Tools that increase the quality of building materials, construction products, works and services are standardization, metrology, certification. In this regard, in many countries the use of these tools applies the relevant legislation. Currently in practice in the market of construction materials the main three model methods of quality management are used. The Address Of The President Of The Republic Of Kazakhstan N. Nazarbayev to people of Kazakhstan «the Third modernization of Kazakhstan: global competitiveness» notes that urbanization processes necessitate the development of the construction sector. It must become a full driver of the domestic economy.